Constructionism and error analysis to understand and improve written english composition of thai software engineering students - Saeheaw T. (Inderscience Enterprises Ltd., 2014)
To improve Thailand's higher education students' written English skills, this paper presents a learning innovation: the remedial framework targeting software engineering students, by integrating constructionism philosophy and leverages error analysis as a key mechanism to assess students' writing. Results show the most common errors are capitalisation, noun phrase, verb phrase, semantic word selection, determiner phrase, calque, and plural-s. The assessment of a pretest and posttest written exercise was statistically significant improvements. This paper suggests that the new framework and assessment technique can improve Thais' written English by shifting from the grammar-based learning method to reach higher levels of learning. © 2014 Inderscience Enterprises Ltd.